Virtual worlds in education – best practice, design and research considerations - Turcsányi-Szabó, Márta; Csízi, Ladislav; Végh, Ladislav (Teaching Mathematics and Computer Science, 2012)
The article briefly describes and characterizes the virtual worlds, different kinds of virtual worlds and possibilities of their use in education. The virtual worlds beyond the passive learning opportunities offer active, constructive and collaborative learning possibilities as well. In the middle section of this article we present the most common ways of different kinds of learning methods, which are illustrated by practical examples as well. In the final sections of the article we deal with the design research approach of 3D virtual worlds.